The concrete study of the development of childhood and adolescence and its contributions to education - Pereira, Angelina Pandita; Magalhães, Giselle Modé; Pasqualini, Juliana Campregher [UNESP] (My University, 2021)
This paper discusses the concrete study of childhood and adolescence from the contributions of cultural-historical psychology. The concepts of activity, leading activity, social situation of development, accessory lines of development, consciousness, and neoformation are presented in each period of life, seeking to articulate with elements of the Brazilian capitalist reality and its inequalities of class, race and gender. To this end, we went through the three epochs (ELKONIN, 1987) of the development proposed by Soviet studies in a context of struggle for equal living conditions, namely: early childhood, childhood and adolescence. In the presentation of each epoch, we explain the existent challenges for concretely understanding human development in Brazil. And, at the end, we discuss some obstacles currently facing education. It is concluded that the desired development will occur in the presence of conditions that make it possible, involving: i) the broader social context (demands that society offers to our children and young people as well as effective conditions provided for its consummation); ii) the organization of teaching and how it operationalizes these demands in terms of form and content, in order to enhance the development of people, promoting needs and reasons for the emergence of the leading activity and being aware of the effects of class, race and gender inequalities in the development process.
O estudo concreto do desenvolvimento da infância e da adolescência e suas contribuições para a educação
Keywords: Adolescence; Childhood; Concrete psychology; Human development; Periodization